Influence of Heat Treatment on Internal Friction Spectrum in NiTiCu Shape Memory Alloy. (2015) - Fabregat-Sanjuan, A.; Ferrando, F.; De la Flor, S.
Abstract: Internal friction (IF) and storage modulus evolution during the martensitic transformation were measured using the DMA technique in order to compare the effect of heat treatment on the behavior of IF in Ti44.6Ni5Cu (%at.) shape memory alloy. Two kinds of experiment were performed: IF measurements as a function of temperature and IF measurements at a fixed temperature to obtain the static term of the intrinsic internal friction. The results are compared with those obtained from DSC measurements. IF results show a clear dependence on the temperature of the heat treatment with distinctive regions that could be attributed to microstructural changes.